A Review of Pathogens, Diseases, and Contaminants of Muskrats (Ondatra zibethicus) in North America - Ganoe, Laken S.; Brown, Justin D.; Yabsley, Michael J.; Lovallo, Matthew J.; Walter, W. David (Frontiers in Veterinary Science, 2020)
Over the last 50 years, significant muskrat (Ondatra zibethicus) harvest declines have been observed throughout North America. Several theories for the decline have been proposed, including increased parasite infections and disease within muskrat populations. No existing wholistic review of muskrat exposure to pathogens, contaminants, and diseases exists. To address this knowledge gap, we conducted a thorough review of existing literature on muskrat pathogens, contaminants, and diseases across their natural range. This review is comprised of 129 articles from 1915-2019 and from 27 U.S. states and 9 Canadian provinces. A wide diversity of contaminants, toxins, and pathogens were reported in muskrats, with the most common diseases being cysticercosis, tularemia, Tyzzer’s disease, and biotoxin poisoning from cyanobacteria. This review provides a summary of muskrat pathogens, contaminants, and diseases over a century that has observed significant population declines throughout the species’ range in North America. Such data provide a baseline for understanding the potential role of disease in these declines. In addition, these data highlight critical knowledge gaps that warrant future research efforts.